2018
DOI: 10.1103/physrevb.97.195407
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of silicene, Si/Ag(111), and Si/Ag(110)

Abstract: We present a state-of-the-art study of the optical properties of free-standing silicene and of singlelayer Si 1D and 2D nanostructures supported on Ag(110) and Ag(111) substrates. Ab initio simulations of reflectance anisotropy spectroscopy (RAS) and surface differential reflectivity spectroscopy (SDRS) applied to the clean Ag surface and Si/Ag interfaces are compared with new measurements. For Si/Ag(110) we confirm a pentagonal nanoribbon geometry, strongly bonded to the substrate, and rule out competing zigz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
(91 reference statements)
2
39
0
Order By: Relevance
“…The solution of the Bethe-Salpeter equation on top of DFT-GW is the state-of-the-art first principles approach to calculate neutral excitations in solid-state systems [1], with successful applications to, molecules [55,72], surfaces [73,74], two-dimensional materials [75,76], and nanostructures [77,78], including biomolecules in complex environments [79,80]. The BSE is a Dyson equation for the four point response function L. It can be rewritten as an eigenproblem for a two-particle effective Hamiltonian H 2p in the basis of electron and hole pairs |eh .…”
Section: Optical Absorptionmentioning
confidence: 99%
“…The solution of the Bethe-Salpeter equation on top of DFT-GW is the state-of-the-art first principles approach to calculate neutral excitations in solid-state systems [1], with successful applications to, molecules [55,72], surfaces [73,74], two-dimensional materials [75,76], and nanostructures [77,78], including biomolecules in complex environments [79,80]. The BSE is a Dyson equation for the four point response function L. It can be rewritten as an eigenproblem for a two-particle effective Hamiltonian H 2p in the basis of electron and hole pairs |eh .…”
Section: Optical Absorptionmentioning
confidence: 99%
“…45 The local density approximation (LDA) was used as in previous successful studies on Si/Ag(110) and Si/Ag(111). 31,46,47 The kinetic energy cutoff was 30 Ry. The theoretical Ag lattice constant of 4.075 Å was used (experiment: 4.085 Å).…”
Section: Gixdmentioning
confidence: 99%
“…34,35 However, rapidly various controversies have emerged about the origin of the various surface reconstructions observed, including (4×4), (√13×√13)R13.9°, (√7×√7)R19.1° and (2√3×2√3)R30° with respect to Ag(111). 23,[36][37][38] First-principles calculations demonstrated that the linear dispersion band observed by ARPES experiments could originate from the hybridization states between silicene and Ag(111) surface. 39 Besides, its impressive stability was definitely ascribed to covalent bonds with the substrate.…”
Section: Introductionmentioning
confidence: 99%